Barriers to early diagnosis and treatment of severely immunosuppressed patients with HIV‐1 infection: A quantitative and qualitative study. Issue 11 (25th December 2020) - Liu, JY; Sun, LQ; Hou, YY; Wang, LF; He, Y; Zhou, Y; Xu, LM; Wang, H; Wang, FS
Abstract : Objectives: To explore the barriers to early diagnosis of HIV infection and timely initiation of antiretroviral therapy (ART). Methods: We assessed the annual number and proportion of ART‐naïve people living with HIV infection (PLWH) with severe immunosuppression in Shenzhen, China, from 2008 to 2019. Selected ART‐naïve PLWHs with severe immunosuppression who were seeking treatment for the first time in the hospital in 2019 were subjected to an in‐depth interview. Results: The proportion of severely immunosuppressed, ART‐naïve PLWH decreased from 36.73% in 2008 to 8.94% in 2015, and then plateaued at approximately 10% from 2015 to 2019. Overall, 55 patients, 70% of whom were men who had sex with men, participated in the qualitative interviews. Ten of them delayed treatment after diagnosis, with a median [interquartile range (IQR)] interval of 5.83 (3.98–8.54) years between diagnosis and ART. More than 80% of the patients reported casual sexual contact within a median period of 6 years and with a median (IQR) of nine (4–20) casual sex partners. The major barriers to HIV testing and diagnosis included lack of knowledge about HIV and high‐risk behaviours, low awareness about HIV testing, and resistance to HIV testing. The major barriers to ART initiation included lack of knowledge about the importance of ART and change of national ART eligibility policy, and HIV‐related stress. Conclusions: The number of PLWHs with severe immunosuppression who seek treatment remains high in Shenzhen, China. Thus, current HIV‐related care programmes targeting access to early diagnosis and treatment need to be improved.